2015
DOI: 10.1016/j.jmva.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Parametric and nonparametric bootstrap methods for general MANOVA

Abstract: a b s t r a c tWe develop parametric and nonparametric bootstrap methods for multi-factor multivariate data, without assuming normality, and allowing for covariance matrices that are heterogeneous between groups. The newly proposed, general procedure includes several situations as special cases, such as the multivariate Behrens-Fisher problem, the multivariate one-way layout, as well as crossed and hierarchically nested two-way layouts. We derive the asymptotic distribution of the bootstrap tests for general f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 37 publications
1
87
0
2
Order By: Relevance
“…The simulation results presented in the supplementary materials indicate that the methods proposed here are rather robust in this regard. Also, in simulations by Konietschke et al (2015, Figure 1), leptokurtic distributions had a larger effect on the power of classical tests without resampling than on tests involving parametric or nonparametric bootstrap.…”
Section: Modelmentioning
confidence: 92%
See 4 more Smart Citations
“…The simulation results presented in the supplementary materials indicate that the methods proposed here are rather robust in this regard. Also, in simulations by Konietschke et al (2015, Figure 1), leptokurtic distributions had a larger effect on the power of classical tests without resampling than on tests involving parametric or nonparametric bootstrap.…”
Section: Modelmentioning
confidence: 92%
“…The generalized inverse needs to be used in lieu of the regular matrix inverse since the latter may not exist, which would make the WTS Q N invalid. Konietschke et al (2015) have shown that, under the technical assumptions mentioned above in Section 2, and under H 0 : Tμ = 0, Q N (T) has asymptotically, as N → ∞, a central χ 2 -distribution with degrees of freedom equal to the rank of T. However, they only considered matrices T where the final component is the identity matrix I p (see sec. 4 of Konietschke et al, 2015).…”
Section: Test Statisticsmentioning
confidence: 99%
See 3 more Smart Citations